Relationship between MMP-9 Gene Polymorphism and Intracranial Aneurysm - Wang, Weiwei; Guo, Zhang; Xie, Dahua; Lin, Zhiyong; Lin, Ruisheng (Cellular and Molecular Biology, 2022)
Matrix metalloproteinase-9 (MMP-9) is a gelatinase, which is a member of the MMPs family. We know that MMP-9 is not only an important gelatinase to regulate the extracellular matrix balance, but also one of the most closely related proteases to the pathogenesis of intracranial aneurysm. The purpose of this study is to investigate the relationship between MMP-9 gene polymorphism and intracranial aneurysm. In this paper, 98 patients who were admitted to a hospital from 2018 to 2019 were selected as the experimental group and the control group according to the relevant standards of intracranial aneurysms. The MMP-9 positive and MMP-9 absorbance values between the two groups were compared, so as to determine the concentration of MMP-9 between the two groups. In addition, the gene distribution and gene frequency analysis of the C-1562T promoter region of MMP-9 were carried out. The results showed that in the control group, the gene distribution frequency of CC type was 67% that of CT type was 31% that of TT type was 2%, that of the experimental group was 52%, and that of CT type was 44%. The results showed that there was a correlation between MMP-9 gene polymorphism and intracranial aneurysm.